Factors Encourage People to Ignore Environmental Health: A Study Qualitative of Climate Management, Common People’s Perspective - Adhy Firdaus (Journal of International Conference Proceedings (JICP), 2020)
The flood disaster that hit Indonesia at the beginning of the year 2020 and the earlier haze and forest fires was very shocking and alarming not only Indonesian but also people of neighboring countries. Indonesian did not prepare for these disasters. These disasters are caused by people's ignorance of environmental safety. Indonesian are religious people, they obey religious laws and rules. They come to pray to the Almighty God regularly. Harm nature is forbidden by religion. The phenomena are, even though religions teach to conserve nature, many people still destroy them. The focus of the study was the perceptions of common people concerning the environment. The research questions are what is the people's perception of nature and the environment? What is the situation that encourages people to ignore the environment? What is the level of environmental knowledge of the common people of Indonesia? What is the best way to wake people up and realize the importance of the preservation of nature and living environment? This qualitative study which uses Phenomenological and Grounded Theory approach with in-depth interviews collecting data procedures found 5 main perspectives of people concerning their involvement of environment and climate change, 1) Environment is a Government responsibility, 2) Economics reason, 3) Lack of knowledge and skills of climate change, 4) No spirit of togetherness to conserve the environment, 5) Climate Changes has no instant and direct impact on oneself. This study contributes to the environmental management to understand the resident’s perception of saving the environment or green Earth and the factors of why people ignoring environmental health. Furthermore, the research findings will help the environmentalist can develop the models to awakening the awareness of people to the green environment and make the right action of conserving nature.